PENGARUH MARKETING MIX TERHADAP MINAT BERKUNJUNG KEMBALI PASIEN RAWAT INAP BPJS KESEHATAN DI KLINIK PKU MUHAMMADIYAH H MAHMUD PEMALANG - Wibowo Bagus Saputra; A Rohendi; Kahar Mulyani (Journal of Innovation Research and Knowledge, 2025)
Visits at the PKU Muhammadiyah H Mahmud Pemalang clinic in 2024 were 8,142 outpatients and 2,440 inpatients. These visits are still small compared to the population in Belik sub-district, which is 119,621 people. BPJS Kesehatan services at the PKU Muhammadiyah H Mahmud Pratama clinic are expected to increase patient visits, especially inpatient services for patients who are not affected by the location of BPJS Kesehatan membership members. The number of active BPJS capitation participants at the clinic is currently 3,200 participants. This study uses a quantitative design and is conducted cross-sectionally. The population of this study was 2,440 people. The sampling technique used was incidental sampling with a sample size of 250 people. Data collection used a questionnaire which was then analyzed using multiple regression analysis techniques. Based on the results of the study, it shows that there is a significant influence of the 7P Marketing Mix (Product, Price, Promotion, Place, People, Process, and Physical Evidence) on the decision to revisit BPJS Kesehatan inpatients at the PKU Muhammadiyah H Mahmud Pemalang clinic, both partially and simultaneously. The influence obtained is a positive influence, which means that the better the Marketing Mix implemented, the higher the interest in revisiting inpatients at the PKU Muhammadiyah H Mahmud Pemalang clinic